Etnografi Virtual Etika Penulisan Berita Media Online Sekolah Alam Tunas Mulia Bantar Gebang - Pujanarko, Mung; Yuliasari, Ika Yuliasari; Wedari, Nenden Retno (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
The ethics of news writing is a standard rule in the science of communication, especially the specialty of journalism. The application of news writing ethics is standardized in mass media which contain journalistic works such as print mass media and online mass media. In this research, we will examine the extent to which news writing ethics are applied on the community blog site Alam Tunas Mulia Bantar Gebang community. The virtual ethnographic methodology was applied in this study because the virtual ethnographic method is able to dissect aspects of local community content which produces unique content and has characteristics in community media, in this case the online media community of scavenger children at Alam Tunas Mulia School, Bantar Gebang. From research on the Alam Tunas Mulia Bantar Gebang School Community weblog, researchers found that there was a basic ethical structure or ethical principles of writing and grammar that were sufficient, according to the choice of words (text) in the allocation of simple community news contexts.